Performance-based evaluation of hydrocarbon steel pipes under internal pressure - Çakir, Ferit; Uçkan, Eren; Akbaş, Bülent; Siyahi, Bilge Gokmirza; Kanli, Nuri; Cakit, Ali Riza; Kaskan, Sibel Guven (Springer International Publishing, 2018)
Hydrocarbon steel pipes have undertaken a very important and fundamental role in the oil and gas industries in the world. Although these pipes are simple structural forms, their structural behaviors are very complex and challenging for the structural engineering community. One of the fundamental problems for pipelines is plastic deformations under internal pressure. This study focuses on to develop a methodology for the performance evaluation of hydrocarbon steel pipes under internal pressure. In this perspective, a hydrocarbon pipe, which is used in natural gas pipelines, is modeled by nonlinear finite element model (FEM) and investigated in terms of structural behavior under different internal pressure conditions; operating pressure (100 bar), design pressure (150 bar) and high pressure (250 bar). In order to obtain an accurate solution, the finite element model is calibrated with a hydrostatic test, which is conducted on a pipe under 133 bar. © 2020 Elsevier B.V., All rights reserved.
Keywords: Finite element analysis; Hydrocarbon steel pipes; Internal pressure; Structural behavior of steel pipes